A group looks at Shylock (Oliver Platt) in The Merchant of Venice (Tufts Archival Research Center, 2014)
slide (photograph). Director: Laurence Senelick. Shylock, wearing a white apron and played by Oliver Platt, leads a conversation as others look on in a university production of The Merchant of Venice.